EXPERIMENTAL AND ANALYTICAL INVESTIGATION ON EFFECT OF STATOR WINDING TYPE TO EQUIVALENT CIRCUIT PARAMETERS OF INDUCTION MOTORS - KENTLİ, AYKUT (CENTRAL BOHEMIA UNIV, 2016)
Because of development in technology, the design of electrical machinery is changing. Induction motors, mostly used as electrical equipment, have developed over the years. One analytically studied area is the stator winding. Generally, each manufacturer uses techniques that directly affect the power of motors and thus, motor efficiency. In this study, the effects of three different stator winding types on motor parameters are investigated. Experiments are performed under no-load, load, and locked rotor conditions. Terminal voltage, power per phase, and phase current values are measured. Power and certain parameters are calculated using an equivalent circuit model. Lastly, a comparison of the results is provided.
Keywords: Stator winding; Power; Equivalent Circuit Parameters; EFFICIENCY